2013
DOI: 10.1149/05002.1997ecst
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrocatalytic Performance for Methanol Oxidation via Insertion of Ruthenium Oxide Particles into Pt and Polyaniline-Poly(Acrylic Acid-co-Maleic Acid) Composite Electrode

Abstract: Polyaniline (PANI) is doped with poly(acrylic acid-co-maleic acid) (PAMA) containing HCl to obtain PANI-PAMA film. Platinum particles are deposited into the PANI-PAMA film via electrochemical deposition to obtain PANI-PAMA-Pt composite electrodes. Subsequently, ruthenium oxide (RuO2) particles are incorporated into the composite electrodes by cyclic voltammetry for 20 and 60 cycles to obtain PANI-PAMA-Pt-RuO220 and PANI-PAMA-Pt-RuO260 composite electrodes, respectively. X-ray diffraction analysis explains a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…157 Other polymeric acid dopants, such as poly(acrylic acid), poly(acrylic acid-co-maleic acid), camphor sulfonic acid (CSA), and TFMSA have also exhibited good performance and stability in the DMFC anodes. 88,154,164,165 In addition, doping often leads to change of surface wettability of the p-CPs. It was observed that while sulphuric acid and hydrochloric acid doped PAni NFs produced a power density of 48 mWcm ¡2 and 46 mWcm ¡2 , respectively, CSAdoped PAni NFs generated 51 mWcm ¡2 of power density.…”
Section: P-conjugated Polymers In Dmfcs 31mentioning
confidence: 99%
“…157 Other polymeric acid dopants, such as poly(acrylic acid), poly(acrylic acid-co-maleic acid), camphor sulfonic acid (CSA), and TFMSA have also exhibited good performance and stability in the DMFC anodes. 88,154,164,165 In addition, doping often leads to change of surface wettability of the p-CPs. It was observed that while sulphuric acid and hydrochloric acid doped PAni NFs produced a power density of 48 mWcm ¡2 and 46 mWcm ¡2 , respectively, CSAdoped PAni NFs generated 51 mWcm ¡2 of power density.…”
Section: P-conjugated Polymers In Dmfcs 31mentioning
confidence: 99%
“…π-conjugated polymers have drawn great attention from researchers in recent years due to their wide use in academic and industrial applications, such as electrochromic devices (ECD) [1,2,3], thin-film polymer solar cells [4], sensing materials [5,6], polymeric memory devices [7,8], catalysts for methanol and ethanol oxidation reactions [9,10,11], polymeric light-emitting diodes [12,13], and smart windows [14]. Among them, the benefit of ECDs is their very low power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…π-conjugated polymers (CPs) and oligomers have attracted a great deal of interest due to their suitability for potential applications in supercapacitors [1,2], catalysts [3,4,5], actuators [6], polymer light-emitting diodes [7,8,9], electrochromic devices (ECDs) [10,11,12], polymer solar cells [13], and sensors [14,15,16]. The most commonly studied classes of CPs are poly(phenylene vinylene)s (PPV) [17], polycarbazoles (PCz) [18,19], polythiophenes (PT) [20], polypyrroles (PPy) [21], poly(3,4-ethylenedioxythiophene) (PEDOT) [22], and polyanilines (PANI) [23].…”
Section: Introductionmentioning
confidence: 99%